(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
In recent years, gastrointestinal diseases, particularly gastritis, have become increasingly common among students. The transition to independent living, heavy academic workload, stress, an irregular daily routine, and an unbalanced diet negatively impact the gastrointestinal tract. According to medical observations, gastritis is one of the leading chronic diseases among young people. Gastritis is an inflammatory disease of the gastric mucosa that can be acute or chronic. The main causes of gastritis include irregular meals, consumption of spicy, fried, and fatty foods, excessive fast food consumption, long periods between meals, consumption of carbonated beverages and coffee, stress, and overwork. Students are a particularly vulnerable group, as their lifestyle often does not correspond to the principles of healthy eating.